PROFIL PASIEN LUKA BAKAR BERAT YANG MENINGGAL DI RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI 2011 - DESEMBER 2013 - Giovany, Lisa Giovany; Pamungkas, Kuswan Ambar; ", Inayah (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBurn injury is one of trauma with high number of morbidity and mortality rate that needs comprehensive treatment from acute phase, subacute phase and chronic phase. The high number of mortality rate is commonly due to severe burn injury The death which is caused by severe burn injury usually influenced by good treatment, including patient factor (age, nutrition, sex, and premorbid factor), trauma factor (type, area, depth of burn injury and related trauma) and therapy factor (prehospital treatment and inhospital treatment).This research was aimed to know the profil of dead patient with severe burn injury at Arifin Achmad General Hospital Riau Province during January 2011-December 2013 which consists of mortality rate, age distribution, sex group, etiology and severe burn injury criteria. The research was on observational study using descriptive retrospective design. This study used total sampling method. Samples of this study were all population of severe burn injury patient that fulfilled inclusion criteria. The total samples were 88 cases. This study shows that the mortality rate of severe burn injury patient was 21.6% (19 patients). The age group 10-50 years old (9 patients) (47.4%) and male in sex group (13 patients)(68.4%) were the highest group of severe burn injury that passed away. Fire (52.6%) was the most commonly cause of death patient. The highest criteria of severe burn injury was second-third degree criteria >20% (age <10 years old or >50 years old) (52.6%).Keywords: Severe Burn Injury, Mortality rate